2021
DOI: 10.17516/1998-2836-0226
|View full text |Cite
|
Sign up to set email alerts
|

Bromobenzoylation of Methyl α-D-Mannopyranoside: Synthesis and Spectral Characterization

Abstract: The widening importance of carbohydrate derivatives as unrivaled potential antimicrobial and therapeutic drugs has attracted attentionto the synthesis of mannopyranoside derivatives. In the present study, regioselective 3-bromobenzoylation of methyl α-D-mannopyranoside (1) was carried out using the direct method and gave the corresponding 6-O-(3-bromobenzoyl) derivative (2) in excellent yield. A number of 2,3,4-tri-O-acyl derivatives (3–10) of this 6-substitution product using a wide variety of acylating agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Modifications in sugar moieties, such as ribofuranose or deoxyribofuranose of nucleosides, include changes in sugar substituents, the substitute of oxygen with another atom, and the inclusion of a heteroatom in the sugar ring, ring size variations, and replacement with an acyclic moieties [10][11][12][13][14][15]. These alterations may lead to excellent variations in the biological activity and degree of selective toxicity according to the respective chemical and physical properties of the moieties [16][17][18][19][20][21]. The modified compounds exhibit a broad-spectrum biological activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifications in sugar moieties, such as ribofuranose or deoxyribofuranose of nucleosides, include changes in sugar substituents, the substitute of oxygen with another atom, and the inclusion of a heteroatom in the sugar ring, ring size variations, and replacement with an acyclic moieties [10][11][12][13][14][15]. These alterations may lead to excellent variations in the biological activity and degree of selective toxicity according to the respective chemical and physical properties of the moieties [16][17][18][19][20][21]. The modified compounds exhibit a broad-spectrum biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleoside analogs and nucleobases constitute a pharmacologically diverse family, which includes cytotoxic compounds, antiviral agents, and immune suppressive molecules [15,21,[25][26][27]. Cytidine analog 5-AZA-2 ´-deoxycytidine is utilized to control the growth of neuroblastoma malignant tumor [28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many scientific reports claim that the major chemical bioactive molecules are either aromatic, heteroaromatic, or acyl substituent groups [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In addition, benzene and its derivatives, which contain atoms such as nitrogen, sulphur and halogen are known to improve the biological activity of the parent compound [ 20 , 21 , 22 , 23 ]. It has also been reported that the linking of two biologically active nuclei leads to a new molecule—one that might possibly better display biological activity [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This connection is considered a crucial factor in the process ( Hasan et al, 2022 , Kawsar et al, 2011 , Mahmud et al, 2021a , Mahmud et al, 2021b , Maowa et al, 2021a , Maowa et al, 2021b ). According to a study on the regioselective acylation of carbohydrate derivatives and their antimicrobial activities ( Farhana et al, 2021a , Farhana et al, 2021b ), attaching two or more highly electron-rich heteroaromatic nuclei and aliphatic chains significantly improves the derivatives' antimicrobial activity compared to the parent nucleus ( Banerjee et al, 2018 , Bechlem et al, 2010 , Daina et al, 2017 , Mahmud et al, 2021a , Mahmud et al, 2021b ; Kawsar and Kumer 2021 ).…”
Section: Introductionmentioning
confidence: 99%